واقع العملية التكوينية في نظام التعليم الالكتروني بالمركز التعليم عن بعد الجلفة -انموذجا - بليح عائشة (University of Eloued جامعة الوادي, 2024)
ملخص: إنّ صعوبة التكوين الالكتروني لفئة الأولى من مستوى التعليم عن طريق المراسلة في التكوين المعمم عن بعد في المناطق السهبية "الجلفة ،المسيلة "يخلق نوع من عدم التوافق التعليمي بين أطراف العمليّة التكوينيّة "المتعلم عن بعد ،الأستاذ الإلكتروني ، وإدارة المركز" وهذا الواقع دفعنا إلى البحث هل عدم التوافق التعلم الإلكترني يعوز سببه إلى فئة المتعلمين بما تحمله من مؤشرات "عامل السن ،المنطقة الريفية الرعوية وشبه الرعوية ..،الجهل الكامل لاستعمال الدروس الالكترونية و التعامل مع المواقع ،والحاسب ،عوامل إجتماعيّة تعوق من عمليّة التكوين ".أم عدم التسخير الأفضل للأستاذ الإلكتروني ،أم الخلل يكمن في الإدارة المطبقة لهاته العمليّة التكوينية . Abstract: The difficulty of the electronic configuration of the first category of the level of education by correspondence in the Inclusive configuration in the Areas of the steppe of Djelfa, Mesila, creates a kind of educational incompatibility between the parties of the training process, "the distance learner, the electronic teacher, and the management of the center. This fact has prompted us to research do you the Is the incompatibility of electronic learning in compatibility is are due to the category of learners with its indicators of "age factor, area rural pastoral and semi-pastoral .., ignorance of the use of electronic lessons and dealing with sites, and computer, social factors hamper the process of formation." Or not to make the best use of the teacher's electronic , Or The imbalance lies in the management applied this formative process.
Keywords: المعلم الالكتروني; برنامج مودل; learner; electronic teacher; modal program